How citizens stop riots: analyzing the case of the 2021 Dutch curfew riots - van Bruchem, Marly (Deviant behavior, 2023)
The causes of riots have been extensively researched. Comparatively, little is known about how they are prevented from occurring. We address this gap with a qualitative study of the role of formal and informal guardians in Amsterdam in January 2021, when public disorder was widespread across the Netherlands after the government had announced a curfew to curb the spread of the Covid−19 virus. We used CCTV footage of two gatherings that had elements of disorder and two that occurred without them. We also rely on interviews with 40 so-called "intimate handlers" who were present during these gatherings to understand how they managed them. We find that the presence and actions of intimate handlers collaborating with the police during the gatherings, effectuated through frequent affiliative contacts with the crowd, had direct de-escalatory effects, operative because of their well-developed social community bonds: participants in gatherings avoided jeopardizing these bonds of attachment, which also created a more positive image of the police through citizen-police collaborations. Our findings thus stress the importance of social bonds for the effectiveness of riot prevention and we consider practical implications for public disorder and large-scale crowd management.